LATIHAN ABDOMINAL DRAWING-IN MANEUVER SAMA BAIKNYA DENGAN CORE STRENGTHENING EXERCISE DALAM MENINGKATKAN KEKUATAN OTOT PENYANGGA TUBUH PADA SISWI SMAN 1 GIANYAR - I Gusti Ayu Mega Purwani; Ni Wayan Tianing; I Putu Adiartha Griadhi (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2017)
ABSTRACTThis study aims to determine the effect of abdominal drawing-in maneuver and core strengthening exercise inincreasing the strength of the core muscles performed on female students SMAN 1 Gianyar. The research designused Randomize Pre and Post Test with Control Group Design with sampling technique using simple randomsampling so that 30 samples were divided into 2 groups, the treatment group (abdominal drawing-in maneuver) andthe control group (core strengthening exercise) 3 times a week for 4 weeks. There was a significant increase of coremuscle strength in both groups with mean improvement in treatment group of 64,05 ± 23,6 (p <0,05) and controlgroup was 69,91 ± 23,2 (p <0,05) . Based on paired sample t-test in the treatment group and control group, there wasno significant result (p> 0,05) in both groups which means abdominal drawing-in maneuver practice as well as corestrengthening exercise in increasing the strength of the core muscle.Keyword : Core Muscle, muscle strength, Abdominal Drawing -in Maneuver, Core Strengthening Exercise